A fluorescence-based opto-mechatronic screening module (OMSM) for automated 3D cell culture workflows - Kahl, Melanie; Schneidereit, Dominik; Meinert, Christoph; Bock, Nathalie; Hutmacher, Dietmar W.; Friedrich, Oliver (Biosensors and Bioelectronics: X, 2023)
Cost-effective automated solutions for hydrogel-based 3D cell culture workflows are required to increase throughput, reproducibility and user-independent results. 3D bioprinters can handle viscous biomaterials, however, throughput is low, they are limited to specific biomaterials, and lack post-processing and analysis methods. Conversely, liquid handling robots have higher throughput but miss viscous materials handling capabilities. Furthermore, commercial systems are not only expensive but mostly not ‘open-source’ and hence are not adaptable to specific experimental requirements. The aim of this study was the implementation of an opto-mechatronic screening module (OMSM) for automated 3D cell culture workflows from production to analysis into a previously developed biomanufacturing workstation. An analysis module with a fluorescence wide-field microscope and a motorised XYZ stage was engineered to transport tissue-culture plates from the storage rack of the workstation to the custom-made microscope and to assess fluorescence-based cell parameters. The microscope has two fluorescence channels and a resolution greater than 228 lp/mm. The XYZ-stage achieved an accuracy of 0.8 μm in X-direction (repeatability 2.4 μm) and 1.4 μm in Z-direction (repeatability <0.1 μm). Viability assays and drug-response studies were conducted on 2D and 3D prostate cancer gelatin-methacryloyl hydrogel models demonstrating its capabilities comparable to a conventional fluorescence microscope. Altogether, the integration of an opto-mechatronic screening module into the biomanufacturing workstation enables automated, reproducible, and user-independent production, imaging and analysis of hydrogel-based 3D cell cultures.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Automation; Fluorescence microscope; High-throughput; Hydrogel-based 3D culture models; Open-source; Opto-mechatronic

An open-source technology platform to increase reproducibility and enable high-throughput production of tailorable gelatin methacryloyl (GelMA) - based hydrogels - Eggert, Sebastian; Kahl, Melanie; Bock, Nathalie; Meinert, Christoph; Friedrich, Oliver; Hutmacher, Dietmar W. (Materials and Design, 2021)
Gelatin methacryloyl (GelMA)-based hydrogels have become highly studied as modular tissue culture platforms due to the combination of the bioactivity of gelatin and tailorability of photo-crosslinkable hydrogels. However, current production and characterization workflows still rely on manual, time-consuming, and low-throughput processes, ultimately limiting widespread adaption. To address these challenges, an open-source technology platform is engineered and validated for automated high-throughput production of GelMA-based 3D constructs by integrating automated pipetting capabilities for viscous and non-viscous liquids. Firstly, the platform is applied in combination with inexpensive absorbance measurements to systematically optimize the mixing sequence for GelMA-based precursor solutions. This enables a decrease in the relative standard deviation of the prepared mixtures from 63% to 2.5%, demonstrating a significantly improved reproducibility. Next, the applicability and high-throughput capacity are demonstrated by the reproducible generation of GelMA dilution series with 0.5 and 2% (w/v) concentration steps as well as double network hydrogels consisting of 2% (w/v) alginate and 5% (w/v) GelMA. Finally, a simple and user-friendly methodology is described that integrates Design of Experiments approaches to systematically study the combinatorial effects of material and crosslinking parameters and to establish a parameter library for on-demand production of mechanically defined GelMA-based hydrogels. The platform enables reproducible production and offers an open-source and accessible alternative to high-priced liquid-handling robots and bioprinters.
CRIS-Team Scopus Importer:2021-04-02
Keywords: 3D cell culture; Bioprinting; Gelatin methacryloyl (GelMA); Hydrogels; Open-source; Reproducibility; Tissue engineering

MechAnalyze: An Algorithm for Standardization and Automation of Compression Test Analysis - Kahl, Melanie; Schneidereit, Dominik; Bock, Nathalie; Friedrich, Oliver; Hutmacher, Dietmar W.; Meinert, Christoph (Tissue Engineering - Part C: Methods, 2021)
The mechanical properties of hydrogels, as well as native and engineered tissues are key parameters frequently assessed in biomaterial science and tissue engineering research. However, a lack of standardized methods and user-independent data analysis has impacted the research community for many decades and contributes to poor reproducibility and comparability of datasets, representing a significant issue often neglected in publications. In this study, we provide a software package, MechAnalyze, facilitating the standardized and automated analysis of force-displacement data generated in unconfined compression tests. Using comparative studies of datasets analyzed manually and with MechAnalyze, we demonstrate that the software reliably determines the compressive moduli, failure stress and failure strain of hydrogels, as well as engineered and native tissues, while providing an intuitive user interface that requires minimal user input. MechAnalyze provides a fast and user-independent data analysis method and advances process standardization, reproducibility, and comparability of data for the mechanical characterization of biomaterials as well as native and engineered tissues. Mechanical properties of hydrogels are crucial parameters in the development of new materials for tissue engineering. However, manual assessment is tedious, not standardized and suffers under user-to-user bias. Hence, the here presented stand-alone software package provides analysis and statistics of force-displacement and material geometry data to determine the compressive moduli, failure stress, and failure strain in a standardized, robust, and automated fashion. MechAnalyze will substantially support biomechanical testing of hydrogels as well as engineered and native tissues and will thus, be of appreciable value to a broad target group in regenerative medicine, tissue engineering, but also life sciences and biomedicine.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Compression test; Hydrogel; Mechanical characterization; Reproducibility

Ultra-low-cost 3D bioprinting: Modification and application of an off-the-shelf desktop 3D-printer for biofabrication - Kahl, Melanie; Gertig, Markus; Hoyer, Phillipp; Friedrich, Oliver; Gilbert, Daniel (Frontiers in Bioengineering and Biotechnology, 2019)
3D bioprinting has become a versatile and powerful method in tissue engineering and regenerative medicine and is increasingly adapted by other disciplines due to its tremendous potential beyond its typical applications. However, commercially available 3D bioprinting systems are typically expensive circumventing the broad implementation, including laboratories in low-resource settings. To address the limitations of conventional and commercially available technology, we developed a 3D bioprinter by modification of an off-the-shelf 3D desktop printer, that can be installed within a single day, is of handy size to fit into a standard laminar flow hood, customizable, ultra-low cost and thus, affordable to a broad range of research labs, or educational institutions. We evaluate accuracy and reproducibility of printing results using alginate and alginate/gelatin-hydrogels and demonstrate its potential for biomedical use by printing of various two-and three-dimensional cell-free and mammalian cell-laden objects using recombinant HEKYFP cells, stably expressing yellow fluorescent protein (YFP) as a model system and high-content imaging. We further provide a parts list and 3D design files in STL and STEP format for reconstructing the device. A time-lapse video of the custom-built device during operation is available at https://vimeo.com/274482794.
CRIS-Team Scopus Importer:2019-08-09
Keywords: 3D desktop printing; Alginate and alginate/gelatin-based hydrogel; HEK293; Rapid prototyping; Ultra-low-cost bioprinting technology